Role of Conflict Management Styles on Managers’ Self-Efficiency at Iranian Schools in Tehran Province (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
The importance of management in different segments of workplace and monitoring of organizational behaviours that appear from managers is supercritical and should be considered increasingly. In some cases, the manager may be faced with different issues and difficulties in the management process, and the level of his/ her performance, and efficiency decreases; furthermore, concentrating more on various aspects of the management when the conflict happened is extremely extensive. By the way, the present research focused on the role of conflict management styles on self-efficiency amongst 259 mangers (men and women) who worked at governmental schools in Tehran Province, Iran. Moreover, the researcher collected the data via two questionnaires; which comprised The Conflict Management Questionnaire, which is proposed by Izadi Yazdan Abadi, and The Self-Efficiency Scale that is developed by Sherer. The findings derived from data analyzing in SPSS Software and illustrated there is a significant relationship between conflict management styles with mangers' self-efficiency at school. Additionally, the styles of conflict management included five main styles such as Accommodating, Avoidance, Collaboration, Competing, and Compromising that have a meaningful relationship with Self-Efficiency. The results shown that Collaboration has a positive association with mangers' self-efficiency and increases its level; on the other hand, Avoidance has a negative relation with the efficiency of managers at schools. Besides, with using styles of conflict management in the correct way that obtain via knowing them perfectly, managers can improve their efficiency and achievement; correspondingly, they endeavor to cope with difficulties and issues at the workplace.